2017
DOI: 10.1007/s11064-017-2275-z
|View full text |Cite
|
Sign up to set email alerts
|

The National Institute of Neurological Disorders and Stroke (NINDS) Epilepsy Therapy Screening Program (ETSP)

Abstract: For over 40 years, the National Institute of Neurological Disorders and Stroke/National Institutes of Health-funded Anticonvulsant Screening Program has provided a preclinical screening service for participants world-wide that helped identify/characterize new antiseizure compounds, a number of which advanced to the market for the treatment of epilepsy. The newly-renamed Epilepsy Therapy Screening Program (ETSP) has a refocused mission to identify novel agents which will help address the considerable remaining … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
153
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 110 publications
(154 citation statements)
references
References 31 publications
1
153
0
Order By: Relevance
“…While this model is useful for differentiation of potentially novel ASDs, 12 it should be noted that without repeated administration and testing it is difficult to interpret how these data will translate into clinical pharmacoresistant populations. Therefore, it is not clear whether the effects described herein would continue or change with repeated administration.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While this model is useful for differentiation of potentially novel ASDs, 12 it should be noted that without repeated administration and testing it is difficult to interpret how these data will translate into clinical pharmacoresistant populations. Therefore, it is not clear whether the effects described herein would continue or change with repeated administration.…”
Section: Discussionmentioning
confidence: 99%
“…2 Further, it was observed that tolerance to lamotrigine extended to some sodium channel blockers but not to ASDs with other mechanisms. 12,13 One of the major goals for the development of novel ASDs is to minimize or eliminate side effects at therapeutic doses. 7,8 Further, resistance to one drug can extend to other ASDs, 5,6,10 thus suggesting the potential for this approach as a screening model for drug-resistant epilepsy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Animal testing was performed in a manner consistent with a protocol approved by the Institutional Animal Care and Use Committee at the University of Utah (protocol 12-11011 and 15-10007, PI: Wilcox) [13,14,16,17,18]. …”
Section: Methodsmentioning
confidence: 99%
“…In designing the CDEs and CRFs for pharmacologic studies for epilepsy, this Task Force focused on minimizing the overall burden on researchers who want to use CDEs while still promoting rigor and reproducibility. Herein, we outline the characteristics and components of sound pharmacologic research that are based, in a large part, on the success of the NINDS‐sponsored ETSP . For investigators wishing to evaluate investigational agents or pursue pharmacologic studies for specific patient populations, we encourage the implementation of these CRFs and CDEs with adjustments for the specific model at hand.…”
Section: Rationale For Model Selectionmentioning
confidence: 99%